Biologically active additives in sport diets: benefits and prospects - Golberg, N. D.; Rogozkin, V. A. (Theory and Practice of Physical Culture, 2018)
Biologically active additives (BAA) are presently considered an indispensable part of any sport diet and training system. However, choosing a right mix of healthy and efficient BAA and their administration is never easy due to the widest range of products on the market and still limited knowledge of the metabolic processes and effects and their control tools. The article was intended to overview a range of ergogenic additives from among the most studied and popular in the modern sports plus the most promising for the competitive performance and progress.